Redescription of Naineris aurantiaca (Müller, 1858) and designation of a neotype from the Brazilian coast (Annelida: Orbiniidae) - Alvarez, Ricardo Castro; Da Rocha Miranda, Vinícius; Dos Santos Brasil, Ana Claudia (Zootaxa, 2019)
The genus Naineris differs from other genera of the Orbiniidae in that all its species possess a rounded prostomium and one or two achaetous rings. Currently, 21 species of this genus have been described worldwide, five of which are recorded from Brazil. Naineris aurantiaca is the only species originally described from the Brazilian coast and the original description is the only record of this species. The description is short and vague, making identification difficult. From recent samples obtained in the type locality of Florianópolis, Brazil, we were able to study specimens of Naineris aurantiaca and redescribe the species. Diagnostic characters for this species are the presence of pre- and post-branchial papillae, anterior branchiae in thoracic segments considerably smaller than those of the rest of the body, distinct dorsal sensory organ from chaetiger 12 onwards, the chaetal arrangement of the thoracic neuropodia (crenulated capillaries in a lower oblique row, uncini in an upper oblique row, subuluncini in two anterior transverse rows, and acicular spines in a posterior row), interramal papillae only present on abdominal parapodia, and the presence of furcate chaetae in the abdominal notopodia. Here, we designate a neotype for the species and discuss the morphological variations we observed among specimens.